2019
DOI: 10.1093/mnrasl/slz071
|View full text |Cite
|
Sign up to set email alerts
|

SDSS J094635.06+101706.1: a redshift one, very radio-loud, γ-ray emitting narrow-line Seyfert 1 galaxy

Abstract: As hybrids of narrow-line Seyfert 1 (NLS1) galaxies and blazars, γ-ray emitting NLS1s are important probes of jet physics in the high Eddington-ratio regime. Only very few of them are known to date; the majority of them below redshift z = 0.5. Here we present the identification of the γ-ray emitting AGN TXS 0943+105 (SDSS J094635.06+101706.1) as a high-redshift NLS1 galaxy. It turns out to be one of the radio-loudest NLS1s known, highly variable at all wavelengths, and shows widely extended radio emission at a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
3
19
0
Order By: Relevance
“…RL NLS1s are likely to harbour powerful relativistic jets, which are the predominant origin of the radio, optical, partially X-ray, and in some cases, γ -ray radiation. The discovery of γ -ray emission from RL NLS1s detected by the Fermi Large Area Telescope (LAT) confirmed the presence of relativistic beamed jets in this type of AGNs along with blazars and radio galaxies (Abdo et al 2009a, b, c;Foschini et al 2011Foschini et al , 2015D'Ammando et al 2015D'Ammando et al , 2016Liao et al 2015;Yao et al 2015;Paliya & Stalin 2016;Berton et al 2017;Lähteenmäki et al 2018;Paliya et al 2018;Yao et al 2019). In addition, radio observations of several RL NLS1s with the Very Long Baseline Array (VLBA) showed that they exhibit pcscale radio jets, compact radio morphologies, flat or inverted radio spectra, high brightness temperatures, and a significant degree of polarization (Abdo et al 2009a, b;Gu et al 2015;Lister et al 2018).…”
mentioning
confidence: 91%
“…RL NLS1s are likely to harbour powerful relativistic jets, which are the predominant origin of the radio, optical, partially X-ray, and in some cases, γ -ray radiation. The discovery of γ -ray emission from RL NLS1s detected by the Fermi Large Area Telescope (LAT) confirmed the presence of relativistic beamed jets in this type of AGNs along with blazars and radio galaxies (Abdo et al 2009a, b, c;Foschini et al 2011Foschini et al , 2015D'Ammando et al 2015D'Ammando et al , 2016Liao et al 2015;Yao et al 2015;Paliya & Stalin 2016;Berton et al 2017;Lähteenmäki et al 2018;Paliya et al 2018;Yao et al 2019). In addition, radio observations of several RL NLS1s with the Very Long Baseline Array (VLBA) showed that they exhibit pcscale radio jets, compact radio morphologies, flat or inverted radio spectra, high brightness temperatures, and a significant degree of polarization (Abdo et al 2009a, b;Gu et al 2015;Lister et al 2018).…”
mentioning
confidence: 91%
“…The detection of γ-ray emission in RL-NLS1s by Fermi /LAT is convincing evidence for the existence of relativistic jets in this class of AGNs (Abdo et al 2009;D'Ammando et al 2012;Yao et al 2015Yao et al , 2019Paliya et al 2018;Yang et al 2018;Paliya 2019). Evidence for interactions between kpc-scale jets and ambient gas in CSSs is revealed (O'Dea 1998 for a review), and superluminal motion is also observed in a few CSSs (Cotton et al 1997 for 3C 138;Taylor et al 1995 for 3C 216;Gawroński & Kus 2006 for 3C 309.1), indicating that the beaming effect may impact on some orientation-dependent properties of CSSs (Saikia et al 1995).…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, in addition to a similar doublehumped spectral energy distribution (SED) of some RLNLSy1s with blazars (e.g., Abdo et al, 2009c;Paliya et al, 2013b;Paliya, 2019), a significant fraction of RLNLSy1s especially very radio-loud (R > 100) display blazar-like characteristics such as rapid infrared and X-ray flux variability (Boller et al, 1996;Grupe et al, 1998;Leighly, 1999;Hayashida, 2000;Komossa & Meerschweinchen, 2000;Jiang et al, 2012;Itoh et al, 2013;Yao et al, 2015;Gabanyi et al, 2018), compact radio cores, high brightness temperature, superluminal motion, flat radio and X-ray spectra (Yuan et al, 2008;Orienti et al, 2012;Berton et al, 2018;Lister, 2018). All these characteristics give indirect evidence of the presence of jets in them and detections of γ-ray emissions by Fermi-Large Area Telescope (Fermi-LAT) 1 from a handful of RLNLSy1s support the scenario that these jets are relativistic (Abdo et al, 2009a,b,c;Foschini et al, 2010;Foschini, 2011;D'Ammando et al, 2012D'Ammando et al, , 2015Yao et al, 2015;Paliya et al, 2018;Yang et al, 2018;Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 94%